Spatial fluctuations of optical solitons due to long-range correlated dielectric perturbations in liquid crystals - Bolis, S; Gorza, S; Elston, S; Neyts, K; Kockaert, P; Beeckman, J (American Physical Society, 2017)
Starting from the de Gennes theory of director fluctuations in nematics, we report on a model of the spatial fluctuations in nematicon propagation. We demonstrate that, when the long-range correlation that characterizes nematic liquid crystals is taken into account in the thermal noise, it is possible to account for the spatial oscillations and propagation losses experienced by nematicons. Increasing the power of the nematicon, the oscillation amplitudes increase and the propagation losses decrease. The nematicon is then more strongly confined and deviates more, but is less scattered by the thermally induced perturbations of the refractive index. All the results are in good agreement with the experimental observations